O processo de desindustrialização nas regiões brasileiras (2000-2016) - Bacik, Rita de Cássia (2018)
Industrialization is defined as the industrial sector being the most dynamic sector in an economy. However, there can be a loss of importance of this sector in both creating jobs and adding value to the economy, leading to a deindustrialization phenomenon. Authors such as Feijó (2007), Bresser Pereira (2008), Oreiro (2011), Cano (2012) claim that Brazil has been facing a deindustrialization process through the last years. Considering the spacial width and the regional diversities in the country, it is presumed that, comparing the brazilian regions each other, the deindustrialization process is different. It is possible that the macroeconomic policies affect the brazilian regions in different ways, and also those regions have different economic structures and industrial policies. Therefore, the main objective in this research is to analyse the dynamic of the deindustrialization process in the brazilian different regions in the 2000-2016 period. This is an exploratory, qualitative-quantitative secondary data research.Books, magazines, papers, content providors and websites were taken to make the bibliografic research and build the theoretical part of this paper. The indicators were selected by the data contained in the bibliography. Four economic indicators were chosen to accomplish the research: the industrial employment share over the total amount of employment, the total amount of the processing and extractive industries’ added value in the GDP and the imports and exports’ trends. The techniques to analyse such data were made by the descriptive and inferential analysis. The descriptive one were made by a graphic description of each region’s data’s idiosyncrasies. The inferential analyses were request the accomplishment of parametric and non-parametric (it will depend on the data’s idiosyncrasies), to explain whether there are statistical differences among the brazilian regions. The results indicate that the process of deindustrialization was characterized in a diferente way in the regions of the country. The results may contribute to identify the weaknesses and the potential in those regions’ productive structure and industrial policies.